Consideration of chronic pain and current prosthetic satisfaction in above knee amputees - A. Yavari; E. Esfandiari; M. Masoumi; h. saeedi; M. allami (Afarand Scholarly Publishing Institute, 2011)
Background and purpose: Following limb loss, offering rehabilitation, prosthesis, assistive devices and training to restore function for amputee are really important. Chronic pain can cause patient's psychological and physical limitations. Purpose: consideration the chronic pain and prosthetic satisfaction of war related amputees Method and Materials: For this study, 38 Iranian above knee amputees were asked to answer the Persian version of prosthesis Evaluation Questionnaire (PEQ) and repot satisfaction of their current prosthesis. Results: Phantom sensation was reported in 78.95%, phantom pain in 60.53%, residual limb pain in 44.74%, lateral limb pain in 76.32% and back pain in 60.53% of patients with lower limb amputation18.38% of patients were really satisfied of their current prosthesis. Conclusion: According to this study, the most prevalent outcomes in war related amputees were phantom sensation, countralateral limb pain, phantom pain, back pain and residual limb pain. More than half of the patients were satisfied of their current prosthesis more than moderate.